Análisis framing durante la campaña electoral presidencial de ecuador 2021 en el diario el comercio versión digital, período noviembre 2020 – abril 2021 - María José, Valencia Lara. (2022)
Abstract Ecuador’s 2021 presidential election campaign was marked by two problems that affect the country: cases of corruption from previous governments, which also had an unbridled wave during the pandemic; and the health, economic and social crisis due to the Covid-19 pandemic. Therefore, by applying the framing theory, the media frames applied by “El Comercio” newspaper in the content published on its web platform from November 2020 to April 2021 were determined. This research work is qualitative and descriptive, the scientific and analytical method was applied to a sample of 32 publications chosen by means of the conglomerate sampling method, in case of presenting something related to: Electoral process in general, corruption, or matters of public interest (triple crisis). For the collection of information, the content analysis technique was used, through a matrix of 33 items that allowed evaluating the frequency of use of the attributes that later formed two frames: “the economic reactivation of the country as a strategy to combat the consequences of the global Covid-19 pandemic” and “the eradication of corruption as a solution to problems that stop the progress of the country” In addition, Dr. Palmira Chavero and B.A. Geovanny Carrasco made an important theoretical contribution from the communication and politics side, respectively. Emphasizing the relevance of the framing theory in the political sphere and public opinion. Keywords: Media framing, public opinion, presidential elections, editorial line. Firmado electrónicamente por: WASHINGTON GEOVANNY ARMAS PESANTEZ Reviewed by: